2019
DOI: 10.1021/acs.est.9b02170
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Utilization of Nano-Fe(0) Embedded in Mesoporous Carbon for Activation of Peroxydisulfate

Abstract: Nanoscale zerovalent iron (nZVI) particles have received much attention in environmental science and technology due to their unique electronic and chemical properties. However, the aggregation and oxidation of nZVI brings much difficulty in practical application of environmental remediation. In this study, we reported a composite nano-Fe(0)/mesoporous carbon by a chelation-assisted coassembly and carbothermal reduction strategy. Nano-Fe(0) particles with surface iron oxide (Fe 2 O 3 •FeO) were wrapped with gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(38 citation statements)
references
References 49 publications
3
35
0
Order By: Relevance
“…1b shows the diffractograms of the nano-ZVI@C and nano-ZVI@C-N catalysts obtained upon calcination of the corresponding MOFs at 800 ºC. The peaks at ~45º, ~65º and ~82º can be attributed to (110), ( 200) and ( 211 [45] or Fe3O4 [62] upon carbothermal reduction has also been reported considering other reactants.…”
Section: Characterization Of the Synthesized Catalystsmentioning
confidence: 69%
See 2 more Smart Citations
“…1b shows the diffractograms of the nano-ZVI@C and nano-ZVI@C-N catalysts obtained upon calcination of the corresponding MOFs at 800 ºC. The peaks at ~45º, ~65º and ~82º can be attributed to (110), ( 200) and ( 211 [45] or Fe3O4 [62] upon carbothermal reduction has also been reported considering other reactants.…”
Section: Characterization Of the Synthesized Catalystsmentioning
confidence: 69%
“…S10 reveal that the relationship between their performance and the nature -21-and abundance of the iron-based structures present in the rods, especially with nano-ZVI, was quite straightforward. The presence of the latter particles, which are essential to ensure the Fe(III) reduction [45,68], was clearly greater when the pyrolysis temperature was increased from 650 to 800 ºC, as deduced from the higher intensity of the peaks, in particular that at ~45º.…”
Section: Performance Of Raw and Calcined Catalysts For Gemfibrozil Removalmentioning
confidence: 95%
See 1 more Smart Citation
“… Tavasoli et al (2008 ) reported that Co/CNT catalysts prepared from the impregnation method exhibited much larger activity than Co/Al 2 O 3 on hydrocarbon yield, which can be ascribed to the weak interaction between Co species and CNT. In addition, mesoporous carbon (MC) using mesoporous silica as a precursor has also received much attention on FTS owing to its ordered pore structure and large surface area ( Wu et al, 2019 ). Zhao et al (2020 ) prepared Co/MC-1300 (where MC was prepared from pyrolysis of furfuryl alcohol and SBA-16 as the hard template), which showed improved cobalt reducibility and C 5+ selectivity up to 74%.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the zero-valent-iron (ZVI, Fe 0 )-based materials in disperse mediums by modified techniques (pre-magnetized [12] , sulfidated [13] , loaded/embedded [14] , micro/nano [15] ) or in stationary phase ZVI (e.g. foamed-ZVI (Fe 0 f ) consisting of three-dimensional porous form ( Fig.…”
Section: Introductionmentioning
confidence: 99%